Renewable Energy in Finland 2055: Strategic Roadmap for Land Use, Regional Development and Geopolitical Dimensions of the Energy Transition - Routa, Johanna; Höysniemi, Sakari; Aakkula, Jyrki; Eerikäinen, Nelli; Hannula, Ilkka; Kautto, Niina; Kohl, Johanna; Lehto, Jani; Lintunen, Jussi; Luukkonen, Saara; Mikkola, Olli-Matti; Niinistö, Tuomas; et al. (Luonnonvarakeskus, 2026)
Finland’s energy system is undergoing a transformation. Climate goals, geopolitical uncertainty and technological progress are driving the shift away from fossil energy towards a more renewable, electrified and integrated energy system. The strategic roadmap produced in the Natural Resources Institute Finland’s REPower research project examines the role of renewable energy in Finland by 2055. The aim of the roadmap is to support decision-making and long-term strategic foresight among significant uncertainties regarding the development of the energy system. The roadmap’s vision is to establish an energy system for Finland that is sustainable and supportive of comprehensive security by 2055. Finland starts from a strong position: in 2024, the share of fossil-free electricity generation based on nuclear, hydropower, wind power, and bioenergy rose to 95%, wind power generation exceeded 20 terawatt-hours (TWh), and the energy system was no longer dependent on energy imports from Russia. The roadmap does not present a forecast; rather, it examines three alternative future pathways, all based on the assumption that carbon neutrality will be achieved by 2050. These pathways are grounded in the greenhouse gas accounting methods in use at the time of writing. Ongoing changes to the accounting framework, particularly in the land-use sector, may affect the calculated timing of carbon neutrality, underscoring the importance of gradual, flexible, and proactive energy policy steering. The pathways differ in terms of the structure of the energy system, the role of renewable energy, the scale of investments, the use of natural resources, and their regional and geopolitical impacts. The EU compliance pathway is based on the implementation of EU regulatory requirements and moderate growth in wind power. Under this pathway, electricity consumption rises to 152 TWh and wind power generation to 65 TWh. Bioenergy provides system flexibility, and wood fuels remain a significant part of the energy system, particularly in combined heat and power (CHP) production. The bioeconomy pathway emphasises increasing the added value of biomass in line with the cascade principle, thereby encouraging a greater market-driven allocation of biomass to the production of biochar, biogas, and liquid biofuels, as well as to lignin-based materials. Under this pathway, electricity consumption rises to 159 TWh and wind power generation to 72 TWh. The pathway strengthens regional economies and security of supply. The electrification pathway entails large-scale electrification, with data centres, renewable hydrogen, and synthetic fuels increasing electricity consumption to 215 TWh. Wind power genera- tion reaches 134 TWh, including 14 TWh from offshore wind. The pathway requires substantial investments and integrates Finland more closely into European energy markets. The energy transition is examined through three interconnected areas of change. In terms of land use and resources, the expansion of renewable energy increases the pressure on land use, especially from the perspective of wind power siting. The development of wind power has significant impacts on land and marine biodiversity, which is why management of nature impacts requires projects to systematically apply a mitigation hierarchy. In all pathways, the role of bioenergy is increasingly focused on the flexibility and security of supply of the system. Regional justice is undermined by the concentration of wind power investments in western Finland, while eastern Finland is left out due to radar constraints, among other things. Successful transition requires inclusive planning practices and fair sharing of the costs and benefits. Geopolitical decoupling from fossil energy strengthens strategic autonomy, but the dependence of clean energy technologies and critical raw materials on China introduces new vulnerabilities. This emphasises closer coordination between energy, foreign, and security policy. Strategic choices are structured across three timeframes: in the short term (2026—2029), establishing a framework for managing land use and strengthening the acceptability of energy projects; in the medium term (2030—2039), resolving the allocation of bio- mass resources and the scale of renewable energy; and in the long term (2040—2055), developing and deploying technical carbon sinks, deepening international integration and strengthening Finland’s role as an exporter of clean energy. The roadmap extends to 2055, with Finland achieving carbon neutrality by 2050 in the future pathways. Furthermore, the report includes observations on the additional measures that would be required to achieve carbon neutrality by 2035. The additional measures complement the long-term assessment but are not part of the actual pathways. The key message of the roadmap is that it is possible to implement the energy transition in an ecologically, economically and socially sustainable way — but only if the transition is strategic, holistic and carried out with an awareness of the uncertainties.
Keywords: energy; biomass; wind power